Analisis Potensi Sektor Jasa Perhotelan dan Pariwisata di Bursa Efek Indonesia Periode 2010-2014: Perspektif Ekonomi Secara Makro - Anggreini Restika Santi; Veny Anindya Puspitasari (Jurnal Hospitality dan Pariwisata, 2017)
Hospitality and tourism companies have been growth very fast. Many people from foreign country have an interest to visit Indonesia. Tourism growth in Indonesia reach 9,39% in 2014, exceeding economic growth rate 5,7%. This high number has influenced hospitality sector. In 2014, investment value on hospitality and tourism sector has achieved US$ 130,13 million consisting of foreign investment US$ 117,24 million and domestic investment US$ 12,86 million. In this paper we examine how hospitality and tourism sector in the BEI from the macro economy perspective. Macro variable used in this research are exchange rate, inflation rate, interest rate, and systematic risk. These variables will be related with the stock price of the hospitality and tourism companies listed in BEI. Keywords: exchange rate, inflation rate, interest rate, systematic risk, stock price, hospitality and tourism sector